Echocardiographic Evaluation of the Right Atrial Area Index in Dogs with Pulmonary Hypertension. (28th January 2018) - Vezzosi, T.; Domenech, O.; Iacona, M.; Marchesotti, F.; Zini, E.; Venco, L.; Tognetti, R.
Abstract : Background: Right atrial area (RAA) is a prognostic factor in human patients with pulmonary arterial hypertension (PAH). Reference intervals for RAA have been described in healthy dogs. Objectives: To evaluate RAA indexed to the body surface area in dogs with PAH as an indicator of right atrial size, PAH severity and right‐sided congestive heart failure (R‐CHF). Animals: A total of 119 client‐owned dogs, 48 dogs with PAH and 71 control dogs. Methods: Prospective observational study. Pulmonary arterial hypertension was classified according to the tricuspid regurgitation pressure gradient (TRPG) as mild (36–50 mmHg), moderate (51–75 mmHg), or severe (>75 mmHg). The RAA index was calculated as the RAA divided by body surface area. Results: The RAA index was higher in dogs with moderate PAH (13.3 cm 2 /m 2 ; range, 3.4–24.7 cm 2 /m 2 ) and severe PAH (12.1 cm 2 /m 2 ; range, 5.4–21.8 cm 2 /m 2 ) than in those with mild PAH (6.7 cm 2 /m 2 ; range, 4.8–10.7 cm 2 /m 2 ) or in controls (7.3 cm 2 /m 2 ; range, 4.2–10.2 cm 2 /m 2 ; P  < 0.001). The RAA index was higher ( P  < 0.0001) in dogs with R‐CHF (17.5 cm 2 /m 2 ; range, 12.7–24.7 cm 2 /m 2 ) compared to those without R‐CHF (7.6 cm 2 /m 2 ; range, 4.4–19.4 cm 2 /m 2 ). The most accurate cutoff value of the RAA index to identify R‐CHF was >12.3 cm 2 /m 2 (sensitivity, 100%; specificity, 89.5%). In dogs with PAH, severity of tricuspid regurgitation (TR) was the only independent predictor of RAA index based on multivariate analysis ( P  < 0.02). Conclusions and Clinical Importance: The RAA index can be used to evaluate right atrial size in dogs and may be more effective than TRPG in predicting R‐CHF in dogs with PAH. The severity of TR is the main determinant of the RAA index in dogs with PAH.